Phase I feasibility study of intraperitoneal cisplatin and intravenous paclitaxel followed by intraperitoneal paclitaxel in untreated ovarian, fallopian tube, and primary peritoneal carcinoma: A Gynecologic Oncology Group Study - Dizon, Don S. (2011)
PURPOSE: Intraperitoneal chemotherapy has shown a survival advantage over intravenous chemotherapy for women with newly diagnosed optimally debulked epithelial ovarian, fallopian tube, or primary peritoneal carcinoma. However, significant toxicity has limited its acceptance. In an effort to reduce toxicity, the Gynecologic Oncology Group conducted a Phase I study to evaluate the feasibility of day 1 intravenous (IV) paclitaxel and intraperitoneal (IP) cisplatin followed by day 8 IP paclitaxel on an every 21-day cycle. METHODS: Patients with Stage IIB-IV epithelial ovarian, fallopian tube, primary peritoneal carcinomas or carcinosarcoma received paclitaxel 135 mg/m(2) IV over 3 hours followed by cisplatin 75 mg/m(2) IP on day 1 and paclitaxel 60 mg/m(2) IP on day 8 of a 21 day cycle with 6 cycles planned. Dose-limiting toxicity (DLT) was defined as febrile neutropenia or dose-delay of greater than 2 weeks due to failure to recover counts, or Grade 3-5 non-hematologic toxicity occurring within the first 4 cycles of treatment. RESULTS: Twenty of 23 patients enrolled were evaluable and nineteen (95%) completed all six cycles of therapy. Three patients experienced a DLT consisting of infection with normal absolute neutrophil count, grade 3 hyperglycemia, and grade 4 abdominal pain. CONCLUSIONS: This modified IP regimen which administers both IV paclitaxel and IP cisplatin on day one, followed by IP paclitaxel on day eight, of a twenty-one day cycle appears feasible and is an attractive alternative to the intraperitoneal treatment regimen administered in GOG-0172.